2018
DOI: 10.1007/s00415-018-8814-y
|View full text |Cite
|
Sign up to set email alerts
|

Noisy vestibular stimulation improves vestibulospinal function in patients with bilateral vestibulopathy

Abstract: The present findings allow to identify the mechanism by which nGVS appears to stabilize stance and gait performance in patients with BVP. Accordingly, nGVS effectively lowers the vestibular threshold to elicit balance-related reflexes that are required to adequately regulate postural equilibrium. This intervention is only effective in the presence of a residual vestibular functionality, which, however, applies for the majority of patients with BVP. Low-intensity noise stimulation thereby provides a non-invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 21 publications
2
40
0
2
Order By: Relevance
“…The rationale behind this phenomenon is a mechanism known as stochastic resonance (SR), according to which the response of a non-linear system to weak input signals can be optimized by the presence of a particular level of stochastic interference, i.e., noise 5,6 . SR-like phenomena in the vestibular system can be induced by an imperceptible noisy galvanic vestibular stimulation (nGVS), which was shown to effectively lower thresholds for vestibular motion perception and vestibulospinal reflexes [7][8][9][10][11] . The therapeutic potential of nGVS was further explored in patients with vestibular hypofunction that suffer from pathologically increased thresholds for vestibular information processing 12,13 .…”
mentioning
confidence: 99%
“…The rationale behind this phenomenon is a mechanism known as stochastic resonance (SR), according to which the response of a non-linear system to weak input signals can be optimized by the presence of a particular level of stochastic interference, i.e., noise 5,6 . SR-like phenomena in the vestibular system can be induced by an imperceptible noisy galvanic vestibular stimulation (nGVS), which was shown to effectively lower thresholds for vestibular motion perception and vestibulospinal reflexes [7][8][9][10][11] . The therapeutic potential of nGVS was further explored in patients with vestibular hypofunction that suffer from pathologically increased thresholds for vestibular information processing 12,13 .…”
mentioning
confidence: 99%
“…Most commonly, this was VOR restoration (for vestibular implants) and postural sway (for nGVS) (Tables 2 and 3). Improvements in dynamic visual acuity, postural sway control, vestibulospinal function and gait speed were also shown to improve after vestibular stimulation [14,31,40,44]. Moreover, a randomised control trial showed improved balance control was also reported in healthy patients after nGVS [39].…”
Section: Discussionmentioning
confidence: 86%
“…It has also been demonstrated that using different configurations of stimuli can assist balance in both the sagittal and frontal planes [30]. However, the mechanism of nGVS means that patients with no residual vestibular function, although few in number, would fail to benefit from this treatment [31].…”
Section: Galvanic Vestibular Stimulation (Ngvs)mentioning
confidence: 99%
See 2 more Smart Citations